New fossil vertebrates from the López de Bertodano Formation (Maastrichtian), of the Seymour Island (=Marambio), Antarctica - O´Gorman, José P. (2017)
Fil: O´Gorman, José P. Museo de La Plata. División Paleontología Vertebrados. Buenos Aires, Argentina.